The Impact Of Process Improvement, Elimination Of Non-Value Added Activities, And Cost Efficiency On The Implementation Of Activity Base Management At Hotel Dhika Serenity Jatinangor - Putri, Adistie Prestiani; Kusniawati, Amelia; Fauzi, Yunta Nur; Arsy, Awlya Hamlatul; Hendrawanto, Dwi Ken (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In an era of competitive and dynamic business competition, the hospitality industry is challenged to maintain its existence through excellent service and operational efficiency. The costs spent by the hotel must really be expenses that add value to the company so that there is no extravagance. Dhika Serenity Hotel is one of the property business lines of Adhi Persada Properti subsidiary of Adhi Karya has the goal of increasing reccuring income and it is located in Jatinangor, Sumedang. The purpose of this study is to try to implement the Activity Based Management method to improve processes, increase efficiency at Dhika Serenity Jatinangor Hotel. The research is used Qualitative-Descriptive method. The results of this study showed that by applying the Activity Based Management method to hotel costs in 2024, it was found that non-value-added activities were quite large after activity management was carried out. The non-value-added activities are Inspection Cost, Electricity Token Purchase, Reservation Process, Resto Order Handling, Helper, Supplier Shortage Shopping. These non-value-added costs can be reduced by 12.99% or equivalent to IDR 343,248,127. So that there are cost savings without reducing the quality of service provided to customers.